2018
DOI: 10.1097/pts.0000000000000527
|View full text |Cite
|
Sign up to set email alerts
|

Associated Factors With Acute Transfusion Reaction From Hospital Online Reporting Events: A Retrospective Cohort Study

Abstract: Objectives In our hospital’s hemovigilance system, a Wi-Fi–based vital signs monitor that automatically transmits data to ensure patient safety has been implemented. We derived the potential clinical characteristics for subsequent association of acute transfusion reactions (ATRs) using the hospital information system database. Methods We retrospectively analyzed multiple factors to identify the possible associations between clinical factors and developing ATRs. The followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…5 , 6 In this study, the incidence of ATR was encountered in 12 patients (6.6%) (95% CI: 3.3–10.7%). This result was in line with previous studies conducted in Bahir Dar, Ethiopia (5.2%), 8 Bangladesh (3.6%), 19 Sweden (7.9%), 27 Tzu-Chi Hospital, Taiwan (3.5%), 24 Belgaum (4.4), 28 Kano, and North-Western Nigeria (3.6%). 29 The result of this study was higher than studies conducted in Iran (0.95), 18 India (0.96%), 1 Namibia (0.2%), 21 Bangalore, India (0.5%), 17 and Democratic Republic of Congo 2.6.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…5 , 6 In this study, the incidence of ATR was encountered in 12 patients (6.6%) (95% CI: 3.3–10.7%). This result was in line with previous studies conducted in Bahir Dar, Ethiopia (5.2%), 8 Bangladesh (3.6%), 19 Sweden (7.9%), 27 Tzu-Chi Hospital, Taiwan (3.5%), 24 Belgaum (4.4), 28 Kano, and North-Western Nigeria (3.6%). 29 The result of this study was higher than studies conducted in Iran (0.95), 18 India (0.96%), 1 Namibia (0.2%), 21 Bangalore, India (0.5%), 17 and Democratic Republic of Congo 2.6.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, factors influencing blood transfusion outcome or complications include abortion history, vital signs, transfused blood component, and the number of transfused units. 8 , 24 To summarize, there was variation in blood component transfusion and ATR across the world. In Ethiopia, there is no hemovigilance system, and whole blood is the most commonly transfused blood.…”
Section: Introductionmentioning
confidence: 99%
“…Since 2010, a wireless vital signs monitoring system (Dinamap ProCare 300 Vital Signs Monitor [GE Medical Systems, Information Technologies, Inc, Milwaukee, WI]) has been integrated into our HIS. 14 The team + mobile application (version 1.8.5.0, designed by team + technology, Taiwan) was used for MEWS scoring (Table 1 ) for real-time warning and notification to physicians and nurses in charge to check patient condition. A total MEWS of 5 or higher indicated that the patient may be at risk of clinical deterioration and may require intensive care.…”
Section: Resultsmentioning
confidence: 99%
“…A group in China reported the successful use of wireless monitoring in patients receiving transfusion. 31 Combining this monitoring of vitals with wearable technology is being pursued to allow better patient flow. The technology appears to be robust, and use is spreading, closing the gap on documentation delay.…”
mentioning
confidence: 99%
“…Notably, dashboards can be viewed anywhere on a web browser. A group in China reported the successful use of wireless monitoring in patients receiving transfusion 31 . Combining this monitoring of vitals with wearable technology is being pursued to allow better patient flow.…”
mentioning
confidence: 99%